Repellency of aqueous and acetone based plant extracts against melon fruit fly, Bactrocera cucurbitae under lab conditions (Zoo Botanica, 2025)
As a cosmopolitan insect pest, melon fruit fly, Bactrocera cucurbiate attacks on many fruits and vegetables. This study was conducted to check the repellent effect of three plant extracts viz; Azadirachta indica, Datura stramonium and Parthenium hysterophorus against melon fruit fly under laboratory conditions. Each plant extract was prepared in two types of solvents i.e water and acetone. Three concentrations (2%, 4%, 6%) of each plant extract (aqueous and acetonic) were applied on bitter gourd fruit, with one positive control (malathion 1ml/L) and one negative control (water/Acetone). The studies revealed that the highest efficacy in aqueous solution was given by Datura stramonium (6.00±0.17% fruit weight loss and 68.86±2.28% repellency) at highest concentration. While in case of acetonic extracts the best results were given by the Parthenium hysterophrous (4.47±0.75% fruit weight loss and 79.276±0.90% repellency). Azadirachta indica was least effective in both types of extract (aqueous and acetonic). Acetone based plant extracts were more efficient as compared to the aqueous solutions except the D. stramonium which was more effective in aqueous based extract. Moreover in both type of extracts efficacy was increased by increasing the concentration.
Keywords: Plant extracts; fruit fly; repellency; Bactrocera cucurbitae